Modulation of inflammatory and hormonal parameters in response to testosterone therapy: Effects on the ventral prostate of adult rats - Mendes, Leonardo O.; Castilho, Anthony C. S.; Pinho, Cristiane F. [UNESP]; Goncalvez, Bianca F. [UNESP]; Razza, Eduardo M. [UNESP]; Chuffa, Luiz Gustavo A. [UNESP]; Anselmo-Franci, Janete A.; Scarano, Wellerson R. [UNESP]; Martinez, Francisco E. [UNESP] (Wiley-Blackwell, 2018)
Testosterone is often recommended in the treatment of several aging-related conditions. However, there are still questions about the consequences of this therapy in terms of hormonal and inflammatory parameters that are crucial for prostate homeostasis. Thus, we investigate if the testosterone therapy (TT) modulates the hormone receptors and inflammatory cytokines in the ventral prostate of adult rats. Wistar rats aging 150 days were divided into two experimental groups (n=10/group): T: received subcutaneous injections of testosterone cypionate (5mg/kg body weight) diluted in corn oil every other day for 4 weeks; and C: received corn oil as vehicle. Animals were euthanized at 180 days old by decapitation. Blood was collected to obtain hormone and cytokines concentrations. The ventral prostate was dissected and processed for light microscope and molecular analyses. Relative ventral prostate weight and epithelial compartment were increased after TT. The number of intact and degranulated mast cells was reduced in the T group. Plasma testosterone, DHT and intraprostatic testosterone concentrations were higher in the T group. TT leads to an increase in cell proliferation and up-regulation of AR, ER, PAR-4, and NRF2. Importantly, plasma concentration and tissue expression of IL-10 and TNF- were higher after TT. In summary, these results indicate that TT can regulate inflammatory response, with impacts in cytokines and mast cell population, and modulates steroids receptors, important parameters for prostatic homeostasis.
Keywords: androgen therapy; androgen receptor; estrogen receptors; interleukin-10; mast cells